(untitled) (Research, Society and Development, 2021)
This study aims to carry out a bibliographic review on the benefits of breastfeeding for women and newborns. It is an integrative literature review, with a qualitative approach, carried out by searching for articles indexed in the Virtual Health Library (VHL), with the help of the following databases: Scientific Electronic Library Online (SCIELO), National Center for Biotechnology Information (PUBMED), Latin American and Caribbean Literature in Health Sciences (LILACS). The inclusion criteria include literature review surveys available in the databases described, between the years 2015 to 2021. As exclusion criteria, they were not considered articles for monetary reward, incomplete and not converging with this study. After applying the inclusion and exclusion criteria, 12 scientific articles remained. The results show that the practice of breastfeeding is of fundamental importance for the mother, child and society, and should always be encouraged and protected. It constitutes a wise natural strategy of bonding, affection, protection and nutrition for the child, generating a great impact in promoting the integral health of the mother / baby couple and, consequently, in reducing infant and maternal morbidity and mortality. It is concluded that breast milk is the appropriate food for the child, both from a nutritional and immunological point of view, as well as at a psychological level, since in addition to favoring the mother-child bond, it offers the nutrients that the child needs to start a healthy life.